Evaluation of Commodity Market Experiences: More Than a Design Issue - Kucukcolak, Necla Ilter (International Journal of Economics and Financial Issues, 2019)
Major benefits of the organized commodity markets will be efficient price formation, transparency improvement, decline in transaction cost and accumulation of expertise in the financial and agricultural sectors. An active spot market is one of the major conditions for the success of a derivative market. This paper studies Turkey’s decentralized spot agricultural markets as well as derivatives market in comparison with its international peers. Based on the outcomes of the analysis, a framework on admission to membership, product design, risk and collateral management mechanisms and quality of warehouse licensing were highlighted for consideration of commodity exchanges. Lack of price correlation between different markets for the same commodity would also contribute to the development of the commodity market. In this regard descriptive and empirical analysis via regression models were made on US and Turkey wheat and cotton markets in relation to product design and the arbitrage opportunities. Keywords: commodity exchange, electronic warehouse receipts (EWR), commodity derivatives JEL Classifications: G10, G23, Q02 DOI: https://doi.org/10.32479/ijefi.7309